The Contribution of the Public Authorities From the Republic of Moldova Towards the Protection and Enhancement of the National Cultural Heritage - Comendant, Vasile (Journal of Legal Studies, 2021)
The article analyzes the contribution of the public administration authorities of the Republic of Moldova towards the protection and enhancement of the national cultural heritage. The competencies of the Parliament, the Executive and Ministry of Education, Culture and Research are investigated as central public authorities in the field of national heritage, as well as the attributions of local public authorities in this field. The attention is on the relationship of cooperation between the central public authorities and the local ones in certain areas. It is underlined the contribution of the European Union's projects towards the reconstruction of some historical value objectives as part of the national heritage. Particular attention is given to the role of cultural heritage in the education of citizens by systematizing the knowledge about national and global cultural heritage.